(3CdajI GdTgjO GdChds - (3GdYGedj, TeS GdOjf, GdTgjO GdChd, GdTgjO GdChd, eMeO Hf ecj Hf eMeO, J (B786(3g` (B1384(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B... (3agPg QSGdI hLjRI aj aQV GdUdGhI (B... (3hgj eQJHI Ydi ebOeI haUhd KdGKI hNGJeI, CeG GdebOeI aGdUdhI GdhGLHIs
(3BNQgG (B:s
(3BNQgG(B: (3hdG JbVi UdhI GdLeYI hdG GdYjO hdG GdBjGJ dZjQ GdYGde HgG eG de jSJhYH GdGMJQGb hdh CWdb GdbVGA Ydi UdGI GdWhGa hGdLfGRI aLGR hcPG GdfPQ GdeWdb(B. (3agPG BNQ eG CQOfG LeYg aj gPg GdQSGdI(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 109s
(3GdPQjYI, L (B2: 167s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis